FACTORS AFFECTING NURSE COMPLIANCE WITH HEALTH PROTOCOL DURING NEW NORMAL COVID-19 IN RS. GL. TOBING TANJUNG MORAWA DELI SERDANG IN 2021 - Nopa Handryani; Tati Murni Karo-karo (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
COVID-19 is a new disease that is transmitted through droplets. The Centers for Disease Control and Prevention (CDC) reports that in the United States the number of health workers exposed to COVID-19 is 133,365 cases with 625 deaths. This study is intended to analyze the factors that influence nurses' non-compliance with health protocols during the new normal covid-19 with an analytical survey design. The research population was 63 nurses using a targeted sampling technique. Chi-Square test analysis and multiple logistic regression were chosen in data processing. The results showed that there was a relationship between the number of years of work (p = 0.020), knowledge (p = 0.001), attitude (p = 0.015), workload (p = 0.001) and the process of health services in the new normal. Multivariate analysis showed that the workload variable was the most dominant variable affecting nurse compliance with health care procedures 5 times the new normal covid-19 (5,230). It is hoped that the hospital will provide education and training on the use of personal protective equipment.